(untitled) (Al-Qamar, 2019)
Imam e Azam Abu Hanifa was known as faqih and mujtahid. However he was a great interpreter of Ahadith. He studied Ahadith thoroughly and he was expert in this art. That’s why all great interpreters have acknowledged his expertise in Hadees. Besides many interpreters have used those Ahadees taken from him. Imam Abdul Razzaq Bin Hammam, the auther of his famous book, Musannaf Abdul Razzaq has citied many Ahadith of Imam Abu Hanifa. In this topic, I have analysed nine Ahadith. I have taken case of giving reference of other interpreters of the mentioned Ahadith. I have taken case of giving referance of other interpreters of the mentioned Ahadith. I have mentioned all referances of Abu Hanifa. By analyzing the mentioned narrations we can approve Imam Abu Hanifa as a faqih, mujtahid as well as a great muhaddis. A lot of interpreters used Ahadith particularly in their narrations originaly taken from him. Imam Abdul Razzaq has mentioned Imam Abu Hanifa’s narrations in his books.